Volume 5: Heat Transfer, Parts a and B 2011
DOI: 10.1115/gt2011-45310
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Measurements of Ingestion Through Turbine Rim Seals: Part 1—Externally-Induced Ingress

Abstract: This paper describes a new research facility which experimentally models hot gas ingestion into the wheel-space of an axial turbine stage. Measurements of CO2 gas concentration in the rim-seal region and inside the cavity are used to assess the performance of two generic (though engine-representative) rim-seal geometries in terms of the variation of concentration effectiveness with sealing flow rate. The variation of pressure in the turbine annulus, which governs this externally-induced (EI) ingestion, was obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 0 publications
3
37
0
Order By: Relevance
“…This is a significant result, as it shows that the simple orifice model from Owen [1] can qualitatively predict ingress not only to an upstream wheel-space where the externally-induced ingress is dominated by the steady-state pressure asymmetry from the vanes, but also downstream where ingress is the result of a less powerful driving mechanism. Figure 10 shows the effect of four flow coefficients, CF = 0, 0.24, 0.29, and 0.36, on the variation The experimental data are fitted with the theoretical effectiveness equations from Sangan et al [11] using the maximum likelihood method described by Zhou et al [12]. All sets of experimental measurements demonstrate good agreement with the theoretical values.…”
Section: Variation Of Concentration Effectiveness With Sealing Flowmentioning
confidence: 78%
See 1 more Smart Citation
“…This is a significant result, as it shows that the simple orifice model from Owen [1] can qualitatively predict ingress not only to an upstream wheel-space where the externally-induced ingress is dominated by the steady-state pressure asymmetry from the vanes, but also downstream where ingress is the result of a less powerful driving mechanism. Figure 10 shows the effect of four flow coefficients, CF = 0, 0.24, 0.29, and 0.36, on the variation The experimental data are fitted with the theoretical effectiveness equations from Sangan et al [11] using the maximum likelihood method described by Zhou et al [12]. All sets of experimental measurements demonstrate good agreement with the theoretical values.…”
Section: Variation Of Concentration Effectiveness With Sealing Flowmentioning
confidence: 78%
“…For any value of Φ 0 , the effectiveness in the downstream wheel-space is higher than that upstream; this indicates a weaker driver for ingress downstream. The experimental data are fitted with the theoretical effectiveness equations from Sangan et al [11] using the maximum likelihood method described by Zhou et al [12]. All sets of experimental measurements demonstrate good agreement with the theoretical values.…”
Section: Variation Of Concentration Effectiveness With Sealing Flowmentioning
confidence: 96%
“…The geometry (not to scale) and boundary conditions are illustrated in Figure 2 The model (including the vane and blade geometries) is based on the design of an experimental rig at the University of Bath described by Sangan et al 1 The rig contains 32 stator vanes and 41 rotor blades, however for simplicity a configuration of 32 vanes and 32 blades has been studied computationally. Hence, an 11.25 degree sector model is considered, having one vane and one blade in the mainstream annulus.…”
Section: Computational Modelmentioning
confidence: 99%
“…The study was carried out prior to an experimental investigation, to be reported elsewhere. 1,2 and the computed flow field information has been used to inform and interpret the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Measured variation of sealing effectiveness " with È o for an axial clearance seal at the design condition 20. (Concentration measurements made on the stator surface at r/b ¼ 0.958 -see inset.…”
mentioning
confidence: 99%